Transitioning to Long-Term Care: Family Caregiver Experiences of Dementia, Communities, and Counseling. (January 2021) - Zmora, Rachel; Statz, Tamara L.; Birkeland, Robyn W.; McCarron, Hayley R.; Finlay, Jessica M.; Rosebush, Christina E.; Gaugler, Joseph E.
Objectives: Previous analyses of interventions targeting relationships between family caregivers of people with Alzheimer's disease and related dementias and residential long-term care (RLTC) staff showed modest associations with caregiver outcomes. This analysis aimed to better understand interpersonal and contextual factors that influence caregiver–staff relationships and identify targets for future interventions to improve these relationships.Methods: Using a parallel convergent mixed methods approach to analyze data from an ongoing counseling intervention trial, descriptive statistics characterized the sample of 85 caregivers and thematic analyses explored their experiences over 4 months.Results: The findings illustrated that communication, perceptions of care, and relationships with staff are valued by family caregivers following the transition of a relative with dementia to RLTC.Discussion: The findings deepen understanding of potential intervention targets and mechanisms. These results can inform future psychosocial and psychoeducational approaches that assist, validate, and empower family caregivers during the transition to RLTC.